1999
DOI: 10.1074/jbc.274.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Human Thymine DNA Glycosylase Binds to Apurinic Sites in DNA but Is Displaced by Human Apurinic Endonuclease 1

Abstract: In vitro, following the removal of thymine from a G⅐T mismatch, thymine DNA glycosylase binds tightly to the apurinic site it has formed. It can also bind to an apurinic site opposite S 6 -methylthioguanine ( SMe G) or opposite any of the remaining natural DNA bases. It will therefore bind to apurinic sites formed by spontaneous depurination, chemical attack, or other glycosylases. In the absence of magnesium, the rate of dissociation of the glycosylase from such complexes is so slow (k off 1.8 ؊ 3.6 ؋ 10 ؊5 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
227
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(252 citation statements)
references
References 37 publications
23
227
0
1
Order By: Relevance
“…Therefore, APE1 most likely displaces TDG because it has even higher affinity for the AP-site than TDG, and in addition APE1 is more abundant. In agreement with this, APE1 strongly stimulates the activity of TDG (Waters et al, 1999). Recent findings indicate, however, that the AP-site binding capacity of TDG might be subject to regulation.…”
Section: Identification Of Tdg and Biochemical Propertiessupporting
confidence: 59%
See 1 more Smart Citation
“…Therefore, APE1 most likely displaces TDG because it has even higher affinity for the AP-site than TDG, and in addition APE1 is more abundant. In agreement with this, APE1 strongly stimulates the activity of TDG (Waters et al, 1999). Recent findings indicate, however, that the AP-site binding capacity of TDG might be subject to regulation.…”
Section: Identification Of Tdg and Biochemical Propertiessupporting
confidence: 59%
“…Such rebinding has subsequently been observed for several DNA glycosylases (Vidal et al, 2001;Waters et al, 1999). Recent studies have, however, demonstrated that the human nuclear UNG2 does not bind AP-sites (Kavli et al, 2002), and the in vivo significance of APsite shielding thus remains elusive, at least for UNG2.…”
Section: The Catalytic Domain Of Ung Proteinsmentioning
confidence: 99%
“…TDG is an intriguing protein that, similar to SMUG1, has a low turnover number and strong binding to AP sites, and its activity is stimulated by APE1. As with SMUG1, the binding of the glycosylase to the AP site inhibits cleavage by the downstream AP endonuclease ( Waters et al 1999). Interestingly, the catalytic efficiency of the protein is increased by SUMOylation (Hardeland et al 2002).…”
Section: Mammalian Uracil-dna Glycosylases and Their Assumed Functionsmentioning
confidence: 99%
“…Uracil-DNA glycosylase inhibitor was obtained from New England Biolabs (Beverly, MA). Assays of UNG activity were done with the single-stranded DNA oligonucleotide substrate and were performed in UNG reaction buffer (20 mM Tris-HCl, 1 mM EDTA, 1 mM dithiothreitol, pH 8.0) at 37°C for 1 h. Apurinic sites were cleaved by adding 1 ⁄2 volume of 0.5 M NaOH and 1 ⁄2 volume of 30 mM EDTA and then boiling for 30 min (27). Samples were then applied to a nondenaturing 20% polyacrylamide gel with electrophoresis at 60 V for 3.5 h or were applied to a denaturing 19% polyacrylamide gel run at 400 V for 2 h. Gels were stained with SYBR Gold (Molecular Probes, Eugene, OR), and nucleic acids were visualized with an ultraviolet transilluminator.…”
Section: Methodsmentioning
confidence: 99%